2021
DOI: 10.21037/acs-2020-mv-86
|View full text |Cite
|
Sign up to set email alerts
|

Transapical off-pump echo-guided mitral valve repair with neochordae implantation mid-term outcomes

Abstract: Background: The NeoChord echo-guided transapical beating heart repair is a promising early-stage minimally invasive surgical procedure for degenerative mitral valve (MV) regurgitation (DMR) correction. The technique has been improved since its inception following procedure standardization, patient selection optimization, and learning curve stabilization. We hereby present the mid-term clinical results through three years of our large single center experience. Methods: All consecutive patients with severe sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The advantage of this therapy is that the length of the ePTFE sutures can be adjusted on the beating heart to maximize leaflet coaptation and to minimize MR, to ensure optimal repair quality finally, according to the real‐time TEE assessment. Up to now, two other transapical artificial chordal implantation devices, Neochord (Neochord, Inc.) and Harpoon (Harpoon, Inc.), have been reported with good safety and effectiveness and stable MR reduction during early‐term and midterm follow‐up 10–16 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The advantage of this therapy is that the length of the ePTFE sutures can be adjusted on the beating heart to maximize leaflet coaptation and to minimize MR, to ensure optimal repair quality finally, according to the real‐time TEE assessment. Up to now, two other transapical artificial chordal implantation devices, Neochord (Neochord, Inc.) and Harpoon (Harpoon, Inc.), have been reported with good safety and effectiveness and stable MR reduction during early‐term and midterm follow‐up 10–16 …”
Section: Discussionmentioning
confidence: 99%
“…Gammie et al 14 reported outcomes in 30 patients with isolated posterior leaflet prolapse using Harpoon system. Colli et al invented a new mitral vavle anatomical classification and concluded that patients with isolated central posterior leaflet and posterior multisegment prolapse benefited more from transapical mitral valve repair by Neochord system 15,16 . Different mitral valve morphologies were included in this initial study to identify optimal mitral valve morphology for further studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations